Peculiarities of use of food fibers in the meat industry - Strashynskyi, Igor; Marynin, Andriy; Ryshkanych, Roman (My University, 2021)
Food fiber plays an important role in the modern world in the field of nutrition, as it has the ability to provide the human body with nutrients that have a positive effect on well-being and overall health.
Keywords: кафедра технології м’яса і м’ясних продуктів; food fibers; cellulose; diseases